Reseña de Busse, Ulrich & Hübler, Axel (2012): Investigations into the Meta-Communicative Lexicon of English - de la Jara Berenjeno, Violeta (Pragmalingüística, 2015)
Se trata de una reseña de Busse, Ulrich & Hübler, Axel (2012): Investigations into the Meta-Communicative Lexicon of English.